Characterization in humans of in vitro leucocyte maximal telomerase activity capacity and association with stress. (15th January 2018) - de Punder, Karin; Heim, Christine; Przesdzing, Ingo; Wadhwa, Pathik D.; Entringer, Sonja
Abstract : The goal of this study was to develop and validate a measure of maximal telomerase activity capacity (mTAC) for use in human studies of telomere biology, and to determine its association with measures of stress and stress responsivity. The study was conducted in a population of 28 healthy young women and men who were assessed serially across two separate days, at multiple time points, and in response to a standardized laboratory stressor. Venous blood was collected at each of these multiple assessments, and an in vitro mitogen challenge (phytohaemagglutinin supplemented with interleukin-2) was used to stimulate telomerase activity in leucocytes. After first establishing the optimal post-stimulation time course to characterize mTAC, we determined the within-subject stability and the between-subject variability of mTAC. The major findings of our study are as follows: (i) the optimal time point to quantify human leucocyte mTAC appears to be at 72 h after mitogen stimulation; (ii) mTAC exhibits substantial within-subject stability (correlations were in the range of r 0.68–0.82) and between-subject variability, with a high intra-class coefficient (0.70), indicating greater between-subject relative to within-subject variability; (iii) mTAC is not influenced by situational factors including time of day, cortisol, acute stress exposure and immune cell distribution in the pre-stimulation blood sample; and (iv) a significant proportion of the between-subject variability in mTAC is associated with measures of stress and stress responsivity (mTAC is lower in subjects reporting higher levels of perceived (chronic) stress and exhibiting higher psychophysiological stress reactivity). Based collectively on these findings, it appears that mTAC, as proposed and operationalized, empirically meets the key criteria to represent a potentially useful individual difference measure of telomerase activity capacity of human leucocytes. This article is part of the theme issue 'Understanding diversity in telomere dynamics'.